BEBERAPA FAKTOR YANG MEMPENGARUHI TINGGINYA KEJADIAN PMS DI LOKALISASI GANG SADAR BATURADENKABUPATEN BANYUMAS TAHUN 2011 - Reviliana, Pipit; Suryandari, Artathi Eka; Fridayanti, Warni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
Sexually Transmitted Diseases (STDs) is one of the Reproductive Tract Infection (ISR) that is transmitted through unprotected sex. Germs that cause these infections can be mold, viruses and parasites. The spread of STDs occur very rapidly throughout the world as well as in Banyumas increasingly alarming. Banyumas position as a transit, tourist and business centers and services in Central Java, making it highly vulnerable to the spread of STDs. Knowing the relationship between economic factors, Sexually Transmitted Infection (STI) clinic services, spiritual and sexual behavior with a sexually transmitted disease incidence in the Localization of BaturadenÂ  Banyumas Gang Sadar Year 2011. This type of analytical research using a survey design with cross-sectional approach in a population of 176 respondents, sampling using a purposive sampling technique with a questionnaire distributed to 64 respondents. The test statistic used is chi square test income commercial sex workers at most have a high income amounting to (71.9%). Sexually Transmitted Infection (STI) clinic services is good enough for most (73.4%). Spiritual commercial sex workers have the most spiritual good less for (78.1%). Sexual behavior of prostitutes at most good enough for sexual behavior (71.9%). The relationship between the economic incidence of STDs there is a significant relationship (p = 0.034). Relationship between Clinical Services with the incidence of STDs there is a significant relationship (p = 0.000). The relationship between the spiritual with the incidence of STDs there is a significant relationship (p = 0.039). Relationship with the incidence of STDs in sexual behavior have a significant relationship (p = 0.000). The results of the analysis then there is a significant relationship between economic factors, Clinical Services Sexually Transmitted Infection (STI), spiritual and sexual behavior with the incidence of STDs. For the community, midwives and health professions continue to add insight, participation and improve the professionalism of health care that could reduce the incidence of STDs. Â  Keywords: The affecting factors of the incident STDs, incident STDs